PERSONALIZATION OF LEARNING AS A CONDITION FOR SUCCESSFUL SOCIALIZATION OF A PERSON IN THE INFORMATION SOCIETY - Anatoly B. Kondratenko (Статистика и экономика, 2016)
The article lays out the methodologicaland theoretical bases of learning takinginto account congenital dominant specialabilities of a person. The employers’analysis of graduates in IT area has been represented, which showed the ﬂ aws in the level of their training and qualiﬁcations. The focus was made on building a model of deﬁning a type of activity of ITspecialists on the basis the project portal«IT specialist».